Smartphone-Based Electrochemical Potentiostat Detection System Using PEDOT: PSS/Chitosan/Graphene Modified Screen-Printed Electrodes for Dopamine Detection - Shen, Xiaoyan; Ju, Feng; Li, Guicai; Ma, Lei (Sensors (Basel, Switzerland), 2020)
In this work, a smartphone-based electrochemical detection system was designed and developed for rapid and real-time detection of dopamine (DA). The system included a screen-printed electrode (SPE) used as a sensor, a hand-held electrochemical potentiostat and a smart phone with a specially designed app. During the detection period, the SPEs modified with poly(3,4-ethylenedioxythiophene) (PEDOT), chitosan (CS) and graphene (G) were used to convert and amplify the electrochemical reaction signals. The electrochemical potentiostat was used to generate excitation electrical signals and collect the electrical signals converted from the sensor. The smartphone—connected to the detector via Bluetooth-was used to control the detector for tests, further process the uploaded data, and plot graphs in real time. Experimental results showed that the self-designed sensing system could be employed for highly selective detection of DA in the presence of interfering substances such as ascorbic acid (AA) and uric acid (UA). CV was carried out to characterize the electrochemical properties of the modified SPEs and the electrochemical behaviors of DA on the modified SPEs. Finally, according to the analysis of DPV responses of DA, the system could detect DA with a detection sensitivity of 0.52 ± 0.01 μA/μM and a limit of detection of 0.29 μM in the linear range of DA concentrations from 0.05 to 70 μM.